System design of a single-chip 2.5GHz low-power WiMAX transceiver - Teo, Jun Xian. (2009)
This report documented the work done by the author for his final year project on the system design of a single-chip 2.5GHz low-power WiMAX transceiver. The baseband equivalent model for a mobile WiMAX IEEE 802.16e transceiver has been addressed in this report. This report analyses and reviews on the latest technology of WiMAX transceiver. It includes the architecture of the WiMAX transceiver and the performance of the existing chipset. It provides the general consideration and building block modelling to design the system of a WiMAX transceiver and tackle the issue to reduce power consumption. System test simulation was performed on a mobile WiMAX transceiver the in terms of Constellation, Power, RF Signal spectrum, Error Vector Magnitude (EVM) and Receiver Minimum Sensitivity Level (RSS). With this behavioural models implemented, the performance of a complete mobile WiMAX transceiver can be evaluated can predicted before an actual hardware design.